Women's Participation in Sustainable Tourism Village Development: Shifting from Tokenism to Meaningful Participation - Fifiyanti, Debby; Nathasya, Nurvia; Africano, Fernando (Politeknik Negeri Bandung, 2025)
This study investigates women’s participation in the development of Burai Tourism Village by integrating Arnstein’s Ladder of Participation and Longwe’s Women’s Empowerment Framework. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and document analysis with 10 purposively selected informants. The findings reveal a structural paradox: women are extensively involved in operational activities within community tourism groups (SORAI, KOI, Purwani), yet remain marginalized in strategic decision-making processes. Their participation is mainly at the consultation and placation levels on Arnstein’s ladder, indicating tokenism rather than transformative engagement. Access to higher rungs—partnership and citizen control—remains limited due to entrenched patriarchal norms within Pokdarwis leadership, which act as institutional barriers to women’s upward mobility. Despite showcasing innovation through educational tourism initiatives and digital adaptation, women's agency is constrained by these structural impediments. This study proposes a multi-pronged empowerment strategy: implementing a 30–50% gender quota in Pokdarwis, enhancing leadership capacity beyond technical skills, establishing women-led cooperatives, and embedding gender perspectives into tourism planning. Theoretically, this research contributes by integrating participatory and empowerment frameworks to reveal how gender norms evolve into structural constraints. Practically, it underscores the urgency of affirmative policies and sustained mentoring to transform symbolic participation into substantive involvement, thereby advancing inclusive and sustainable rural tourism development.